GENETIC DIVERSITY OF Vibrio harveyi ISOLATED FROM TIGER PRAWN Penaeus monodon HATCHERIES AND GROW OUT PONDS - Muliani Muliani; Ince Ayu Khairana Kadriah; Andi Parenrengi; Sulaeman Sulaeman (Indonesian Aquaculture Journal, 2006)
ibrio harveyi is known as one among the most harmful bacteria infecting tiger prawn at every stage of its life’s. The present research was aimed to reveal the genetic diversity of Vibrio harveyi isolated from tiger prawn (Penaeus monodon) culture. The samples of bacteria were collected from hatchery (brood-stock, larvae, natural feed, artemia, and larval rearing water) and grow-out (juveniles, water, shrimp, sediment, plankton, crab, mollusc, microalgae, and wild fish).  The taxonomic identification of Vibrio spp.was performed based on the physiological and biochemical characteristic following the isolation by Thiosulphate Citrate Bile-salt Sucrose Agar (TCBSA) media. Amplified Ribosomoal DNA Restriction Analysis (ARDRA) for 16S-rRNA analysis and Macrorestriction Fragment Length Polymorphism (MLFP) analysis using Pulsed Field Gel Electrophoresis (PFGE) were applied to reveal the genetic diversity of V. harveyi. According to the taxonomic identification, of 361 isolates of Vibrio spp., 129 isolates (35.7%) were identified as V. harveyi. The result of ARDRA analysis showed that the 16S-rRNA gene of V. harveyi digested by RsaI and HhaI enzyme, each generated three and four identical fragments respectively for the all samples. These meaned that ARDRA could not reveal any genetic variation on V. harveyi. The size range of all DNA fragment was less than 500 bp. This result indicated that the high genetic diversity of V. harveyi was revealed by MFLP-PFGE analysis. DNA fragment of V. harveyi was digested by NotI enzyme.